Measurements and applications of δ2H values of wood lignin methoxy groups for paleoclimatic studies - Greule, Markus; Wieland, Anna; Keppler, Frank (Quaternary science reviews, 2021)
Stable hydrogen isotope values of wood lignin methoxy groups (delta H-2(LM)) are increasingly applied to reconstruct the stable hydrogen isotope composition of precipitation (delta H-2(precip)) and mean annual temperatures (MAT) of mid latitudes regions. Recently, the analytical procedure for measuring delta H-2(LM) values was considerably improved by the availability of new reference materials that are in full accordance with the requirements of normalising stable isotope measurements. Using this improved procedure we determined the delta H-2(LM) values of tree rings from 40 geographical locations. Using these values, we present a revised relationship between delta H-2(LM) and delta H-2(precip) which is: delta H-2(precip) [mUr] = (delta H-2(LM) [mUr] thorn 206 mUr)/0.67. In addition, a new equation for reconstructions of MAT is: MAT [degrees C] = (delta H-2(LM) [mUr] thorn 272 mUr)/3.04 [mUr/degrees C]. We provide a simple numerical model that explains the observed biosynthetic isotope fraction pattern between delta H-2(LM) and delta H-2(precip). Finally, we applied the new equations to a previous data set for wood samples collected close to the Hohenpei(sic)enberg Meteorological Observatory in Germany. The data set included a 100-year-chronology (1916-2015) from nine tree ring cores removed from four beech trees. The MAT from delta H-2(LM) values reconstructed for this geographical location was 7.96 +/- 2.17 degrees C and in very good agreement with the observed mean MAT of 7.82 +/- 0.75 degrees C during this time period. Therefore, we conclude that the revised relationships between delta H-2(LM), delta H-2(precip) and MAT provide the basis for reliable application for paleoclimate reconstructions. (C) 2021 Elsevier Ltd. All rights reserved.
Im Titel ist delta als griechischer Buchstabe dargestellt
Gesehen am 24.09.2021